2005
DOI: 10.1093/ajcn/82.4.751
|View full text |Cite
|
Sign up to set email alerts
|

Arterial endothelial dysfunction in baboons fed a high-cholesterol, high-fat diet

Abstract: Our results show that an HCHF diet can directly induce inflammation and endothelial dysfunction. Prior in vivo exposure to an HCHF diet attenuates the in vitro responses of endothelial cells to atherogenic risk factors. This preconditioning phenomenon may have significant clinical relevance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 19 publications
4
29
0
Order By: Relevance
“…This is in accordance with experimental [32],[33] and epidemiological observations [34]. Specifically, there is experimental evidence that addition of minimally-oxidised LDL results in a ≈22-fold increase in levels of MCP-1 in ECs in an in vitro co-culture system [32].…”
Section: Discussionsupporting
confidence: 87%
“…This is in accordance with experimental [32],[33] and epidemiological observations [34]. Specifically, there is experimental evidence that addition of minimally-oxidised LDL results in a ≈22-fold increase in levels of MCP-1 in ECs in an in vitro co-culture system [32].…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, it is believed that the bioflavonoids connect to the elastic fiber components (collagen and elastin) of the blood vessels, increasing their resistance to enzymes [Shi et al, 2005]. In this fashion, leucoanthocyanidins increase the tonus and resistance of the capillary walls, which may have been the reason for the enhancement of liver perfusion found in this study.…”
Section: Discussionsupporting
confidence: 52%
“…[13][14][15] This injury leads to an alteration in the normal functionality of endothelium with a decrease in endothelium-dependent relaxation induced by acetylcholine. 16,17 It has been shown that the relationship between endothelial dysfunction and relaxation response induced by acetylcholine is similar.…”
Section: Discussionmentioning
confidence: 99%